KEPUASAN MASYARAKAT TERHADAP PELAYANAN BUS RAPID TRANSIT (BRT) TRANS SEMARANG DI KOTA SEMARANG DI KORIDOR I MANGKANG-PENGGARON - Mohamad Ardhi Fareza; Fathurrohman Fathurrohman; Dewi Rostyaningsih (Journal of Public Policy and Management Review, 2014)
Semarang is a city that has many residents . The number of people who live or occupy the city of Semarang make the issues that must be faced by the Government of Semarang city , one of which is the problem of congestion . Based on data from the Central Bureau of Statistics the city,the number of vehicles in the city of Semarang until 2011 reached 186.164unit , which consists of two-wheeled vehicles and 151 286 33 523 four-wheeled vehicles . To minimize traffic congestion in the city of Semarang then made mass transport is Bus Rapid Transit ( BRT ) andwho became the first corridor is the major Mangkang - Penggaron .The purpose of this study was to determine the level of community satisfaction with services Bus Rapid Transit ( BRT ) corridor I Mangkang Trans Semarang - Penggaron based on the Ministry of Administrative Reform No. . KEP/25/M.PAN/2/2004 where there are 14 dimensions .Based on the analysis and processing research data shows that public satisfaction with the services of Trans Semarang BRT corridor I get the value of Community Satisfaction Index ( HPI ) of 67.03 and fit in either category. Based on the Cartesian diagram there are two dimensionsthat must be maintained, namely performance dimensions cost reasonableness and appropriateness of the cost, while there are four dimensions given priority so that its performance is improved dimensional speed of service, accuracy of service, comfort and safety services .